The new atheisms from the sociology of religion - Oviedo Torró, Lluís (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The contemporary atheism assumes new features, though his contents follow the guidelines of the traditional atheism. From a more sociological point of view it is possible to describe the so called ‘new atheism’ as a wide social movement, which program and performance turns out to be symmetrical to that of the forms of religious fundamentalism, with similar characteristics. On the other hand it is a movement that follows the guidelines and organization of social networking online. His relationship with the secularization background in advanced societies is complex, because on one hand feeds the current religious crisis, but on the other reframes the question of God in an environment that seemed indifferent or have forgotten her.
Keywords: New atheism; secularization; social movement; sociology of religion; fundamentalism.